Neurological Complications following Blood Transfusions in Sickle Cell Anemia - Hana Alharbi; Nayaab Khawar; Jolanta Kulpa; Anne Bellin; Simona Proteasa; Revathy Sundaram (Case Reports in Hematology)
In Sickle Cell Anemia (SCA) patient blood transfusions are an important part of treatment for stroke and its prevention. However, blood transfusions can also lead to complications such as Reversible Posterior Leukoencephalopathy Syndrome (RPLS). This brief report highlights two cases of SCA who developed such neurological complications after a blood transfusion. RLPS should be considered as the cause of neurologic finding in patients with SCA and hypertension following a blood transfusion.